Comparative pharmacokinetics of a single and double dose of a conventional oxytetracycline formulation in sheep, to allow for therapeutic optimisation - Swan, Gerry E. (University of Pretoria, 2013)
Dissertation (MMedVet)--University of Pretoria, 2008.